Online learning: Attitudes of Russian students - D. V. Rudenkin (Образование и наука)
Introduction. Active using of Internet technologies in the process of learning has become one of the most characteristic trends in the development of Russian education system over the past few years. The spread of this trend is facilitated by both the internal patterns of the development of Russian educational institutions and the need to transfer the learning process to a distance learning format, which arose under quarantine measures due to the Covid-19 pandemic. At the same time, it remains difficult to say, whether this process meets the real needs of students or not.The aim of the article is to identify and describe the main sentiments that arise in the environment of Russian students in connection with the growing role of the Internet in the learning process.Methodology and research methods. The present research is based on a complex methodology and uses both theoretical and empirical methods of analysis. The conceptual framework and the initial hypothesis of the research are determined on the basis of an analytical review of current papers in the area of psychology and sociology of education, which was implemented by using of common scientific methods: analysis, synthesis, comparison, and generalisation. The peculiarities of the actual attitudes of students to online learning were revealed using a mass survey of students in Ekaterinburg (N = 526) and an in-depth psychodiagnostic questionnaire conducted among students at the Ural State Pedagogical University (N = 120).Results. In the course of the research, it was established that the increasing internetisation of the learning process does not correspond to the real needs and patterns of behaviour of the majority of students and is perceived by them rather negatively. It was possible to find out that Russian researchers are used to considering modern students as a special generation of people, who have grown up in the conditions of the widespread spread of Internet technologies, who are accustomed to using such technologies very actively and are in need of their application within the framework of the learning process. However, the analysis of real moods of the students demonstrated that such a view is only partly true. Although many of them are really accustomed to actively using the Internet in their daily lives, most of them do not express real demand for using of it into the learning process.Scientific novelty. The authors substantiate skepticism about the intensive implementation of Internet technologies in the process of learning. The argument for the inconsistency of online learning with the real needs and patterns of behaviour of student representatives is presented. The need to carefully introduce Internet technologies into the learning process is recognised.Practical significance. The research materials can be used for the optimisation of Internet technologies implementation in the learning process and for the clarification of optimal algorithms for using such technologies when working with students.